The usage of green building concept to reduce operating costs (study case of PT. Prodia Widyahusada) - Felix Novendra Tjenggoro; Khusnul Prasetyo (Emerald Publishing Limited, 2018)
The purpose of this paper is to emphasize green building concept usage and its effect on operating costs and uses Grha Prodia, a building with a green concept owned by PT. Prodia Widyahusada.This research will test whether Grha Prodia could earn Leadership in Energy and Environmental Design (LEED) certification based on the aspects that it has and it will also compare the operating costs of Grha Prodia with Prodia Tower. The two main theories used in this research are cost and green building.The result of this research is Grha Prodia is considered as a green building and it could earn LEED certification if the current aspects are continuously implemented and maintained.Moreover, it can fulfill all prerequisite credits in each criterion and further enhance it by fulfilling optional credits in all criteria available. Grha Prodia is also able to demonstrate lower operating costs than a regular building, with 63 percent less water usage and 53 percent less electricity usage.